The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1123/jcsp.2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders in Sport: Comparing Eating Disorder Symptomatology in Athletes and Non-Athletes During Intensive Eating Disorder Treatment

Abstract: The current study tested if athlete patients differed from non-athlete patients in measures of eating disorder (ED) and related pathology. Athlete (n = 91 in Study 1; n = 39 in Study 2) and non-athlete (n = 76 in Study 1; n = 26 in Study 2) patients completed self-report measures, and body mass index (BMI) was calculated. Athlete patients had significantly lower ED symptomatology and depression than non-athlete patients (ps < .05). ED impairment, worry, psychosocial functioning, BMI, obsessive-compulsivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…To our knowledge, no study has examined differences in disordered eating psychopathology between athletes with secondary exercise dependence and those with disordered eating alone. However, in those with a clinical eating disorder, compulsive exercise is associated with greater eating disorder pathology [ 33 , 34 ]. Compulsive exercise represents an urge to perform exercise with the intent to escape anxiety that arises from the imagined negative consequences of not exercising [ 12 ] and better reflects exercise behaviours that are secondary to disordered eating than exercise dependence [ 12 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has examined differences in disordered eating psychopathology between athletes with secondary exercise dependence and those with disordered eating alone. However, in those with a clinical eating disorder, compulsive exercise is associated with greater eating disorder pathology [ 33 , 34 ]. Compulsive exercise represents an urge to perform exercise with the intent to escape anxiety that arises from the imagined negative consequences of not exercising [ 12 ] and better reflects exercise behaviours that are secondary to disordered eating than exercise dependence [ 12 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results also indicated that athletes’ attitudes and expectations regarding an ideal body are modeled by friends and team norms. Thus, another recommendation is to discourage activities and comments that draw attention to athletes’ weight, such as public weighing or comparing athletes’ bodies [17, 27]. Coaches should also intervene when they hear negative body-related comments expressed by athletes on the team.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Risk factors for eating disorders and investigated aspects in the present study [1,3,4,5,18,25,27,29,30,31]…”
Section: Procedures and Measurementsmentioning
confidence: 99%
“…The current study was part of a larger study examining outcomes within an intensive ED treatment program. Psychological measures from this larger study are reported elsewhere (Fewell, Levinson, & Stark, 2017;Fewell, Nickols, Tierney, & Levinson, 2018). A total of 21 male and female athlete patients and 36 male and female non-athlete patients who were enrolled in either residential or partial hospitalization treatment at an ED treatment facility between December 2012 and June 2017 were included in this study.…”
Section: Participantsmentioning
confidence: 99%